Review of Reservoir Damage Mechanisms Induced by Working Fluids and the Design Principles of Reservoir Protection Fluids: From Oil–Gas Reservoirs to Geothermal Reservoirs - Ou Jiang; Ling Cao; Wenxi Zhu; Xiuhua Zheng (Energies)
Various working fluids are applied during geothermal reservoir development, and geothermal reservoir damage induced by contacts between working fluids and reservoir formations are inevitable. Reservoir damage mechanisms, including solid and colloidal plugging, fluid sensitivity, stress sensitivity, and water locking, provide guidance for designing reservoir protection working fluids. In this paper, based on the design principles of reservoir protection working fluids applied in oil–gas reservoirs, four design principles of reservoir protection working fluids are proposed to eliminate potential geothermal reservoir damage for geothermal reservoirs, containing solid-free, facilitated flowback, temporary plugging, and inhibition. Solid-free is achieved by replacing solids with polymers in working fluids. Surfactant and materials with low affinity towards rock surfaces are applied for the facilitated flowback of working fluids from reservoir formations. Temporary plugging is achieved by using temporary plugging materials, some of which are polymers that also apply to solid-free working fluids. Besides, some of the temporary plugging materials, such as surfactant, are applicable for both the facilitated flowback and inhibition of working fluids. The inhibition of working fluids include the inhibition of clay minerals, which can be attributed to clay mineral inhibitors or activity regulators in working fluids, as well as the inhibition of mineral precipitations. This review aims to provide insights for geothermal reservoir protection working fluids, contributing to achieving an efficient development of geothermal resources.